Workers' Education in Canada - Eastman, S. Mack (International Labour Review, 1939)
In continuation of the series of articles devoted to workers* education in different countries, the following survey deals with the movement in Canada. After a brief explanation of the natural and social environment in which the Canadian institutions have grown up, Dr. Eastman, who was himself a pioneer in workers'' education in western Canada, describes the origin and development of the various schemes and the use which is being made of modern facilities such as the radio, and emphasises the need for continuous educational effort in order to enable the workers to keep pace with the rapid changes characteristic of the present age. –Introduction